1993
DOI: 10.1016/0014-5793(93)80027-r
|View full text |Cite
|
Sign up to set email alerts
|

A conformation‐dependent monoclonal antibody against active chicken acetylcholinesterase

Abstract: We show that the C-131 monoclonal antibody, directed agamst chicken AChE, recognizes active chicken AChE, but not the SDS-denatured or heat-inactivated protein.Previous results indicated that C-131 only binds to the active enzyme, and not to inactive molecules which also occur in the embryonic chicken brain. In contrast with C-131, other monoclonal antibodies obtamed in the same series, such as C-6 and C-54, also recognize denatured or inactive AChE. It is noteworthy that these antibodies all seem to react wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The remaining 20 -30% of the enzyme molecules become catalytically active and consist of both stable and unstable forms that transit the secretory pathway to the cell surface where they are inserted into cholinergic synapses such as the neuromuscular junction or nicotinic and muscarinic synapses in the central and peripheral nervous systems. These studies were confirmed by Chatel et al (26) using monoclonal antibodies that could distinguish between catalytically active and inactive AChE, and they showed that in chicken brain at least 30% of the AChE was catalytically inactive, an ER resident, and not trafficked in the Golgi apparatus (27). The mechanisms responsible for the activation and stabilization of AChE subunits into catalytically active oligomers are being elucidated.…”
Section: Discussionmentioning
confidence: 77%
“…The remaining 20 -30% of the enzyme molecules become catalytically active and consist of both stable and unstable forms that transit the secretory pathway to the cell surface where they are inserted into cholinergic synapses such as the neuromuscular junction or nicotinic and muscarinic synapses in the central and peripheral nervous systems. These studies were confirmed by Chatel et al (26) using monoclonal antibodies that could distinguish between catalytically active and inactive AChE, and they showed that in chicken brain at least 30% of the AChE was catalytically inactive, an ER resident, and not trafficked in the Golgi apparatus (27). The mechanisms responsible for the activation and stabilization of AChE subunits into catalytically active oligomers are being elucidated.…”
Section: Discussionmentioning
confidence: 77%
“…The fact that they react with MTP suggests that inactive molecules possess some catalytic activity, with a slower turnover than regular AcChoEase. It is noteworthy that inactive molecules are not recognized by the monoclonal antibody C-131, which appears to be conformation dependent, since its binding is lost together with activity during heat denaturation (24 cosidase H suggests that they are localized in the endoplasmic reticulum. Rotundo et al (9) reported that in chick muscle cultures most of the newly synthesized AcChoEase polypeptides are inactive, sensitive to endoglycosidase H, do not bind WGA, and are rapidly degraded in a nonlysosomal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to carboxyl esterase family of enzymes. It is synthesized in the endoplasmic reticulum and is then exported towards the cellular surface, where its different molecular/globular forms may be anchored in plasma membrane, attached to the basal lamina (asymmetric collagen-tailed forms), or secreted as soluble molecules (nonglobular) forms [ 15 ]. It is reported that dimeric (G) AChE forms are present in the human erythrocytes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%